DETERMINATION OF PSYCHOEMOTIONAL DISORDERS IN PATIENTS WITH DENTAL DEFECTS DURING ORTHOPEDIC TREATMENT - Azimova Shakhnoza Shukhratovna; Saidov Akbar Ahadovich (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation. In recent years, the world dental practice has made significant progress in providing high-quality care to patients. This was facilitated by certain achievements in the study of the etiology of dental diseases, the creation of effective methods of their treatment using the latest achievements in dental materials science and modern medical equipment. At the same time, as clinical experience shows, doctors increasingly have to deal with patients who complain about a poorly manufactured prosthesis, which is, nevertheless, a foreign body, because of the pain and tactile discomfort that occurs in the first time after they are installed in the mouth.